The blood group U antigen is not located on glycophorin B - Ballas, Samir K.; Reilly, Patricia A.; Murphy, Darci L. (Biochimica et biophysica acta, 1986)
Erythrocytes from twelve individuals with the S −s −U − phenotype and from ten with the S −s −U + phenotype were analyzed and compared to control cells with S +/s +U + determinants. No red cell abnormality was detected in S −s −U + or S −s −U − carriers. Sialic acid content was similar ( P>0.05) for S −s −U + and S −s −U − erythrocytes (74.6±7.14 and 71.4±8.53 nmol/10 9 red blood cells, respectively) but significantly less ( P<0.001) than controls with 89.5±11.4 nmol/10 9 red blood cells, N=16. Fluorographs of SDS-polyacrylamide gels showed no glycophorin B in membranes from S −s −U + and S −s −U − erythrocytes labeled with NaB 3H 4. Glycophorins were extracted from red cell membranes in chloroform/methanol, labeled with 125I and analyzed by SDS-polyacrylamide gel electrophoresis. Periodic acid Schiff stain and autoradiographs of these gels also showed absence of glycophorin B in both S −s −U + and S −s −U − cells. These findings suggested that the U antigen is not located on glycophorin B. This hypothesis was tested by deteriming blood group antigenicity on red cell membranes and on extracted sialoglycoproteins by the hemagglutination inhibition technique. Although U and S/s activities were detected in control red cell membranes, extracted glycoproteins demonstrated S/s activity but no U activity. Together the data indicate that both S −s −U + and S −s −U − erythrocytes lack glycophorin B and that the U antigen is not located on glycophorin B. This deletion does not seem to affect the structure-function of the red cell.